Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Influence of institutional factors on the performance of the agricultural sector in Mozambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Abstract: This paper is a review of the institutions and the performance of the agricultural sector in Mozambique, using an analysis table adapted to the assessment of the connections between the institutions and economic development. In the first part, information is presented on the performance of the sector between 2008 and 2017, showing a per capita reduction in productivity and the production of foodstuffs. The second part offers an analysis on the extent to which, and the way that, the development of the sector institutions influenced agricultural performance during that period. There was found to have been institutional instability that affected performance in the sector, which was unable to slow the reduction in production and productivity, which could reflect a wider socioeconomic and institutional environment, i.e. beyond the agricultural sector. The third part looks at some elements for reflection on institutional issues that could contribute to the debate on the future development of the agricultural sector. We refer to the need to think about the future of agriculture in Mozambique from a long-term perspective, focusing on the adoption and stabilization of an institutional framework aimed at increasing agricultural productivity and preserving the environment.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; institutions / instituições

Influência de Factores Institucionais no Desempenho do Sector Agrário em Moçambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Este artigo constitui uma revisão das instituições e do desempenho do sector agrário em Moçambique, aplicando um quadro de análise adaptado à avaliação da ligação entre as instituições e o desenvolvimento económico. Na primeira parte, apresenta-se informação sobre o desempenho do sector entre 2008 e 2017, verificando-se redução da produtividade e da produção per capita de alimentos. A segunda parte oferece uma análise sobre a medida em que, e o modo como, a evolução das instituições do sector influenciou o desempenho da Agricultura nesse período. Verifica-se ter havido instabilidade institucional que afectou o desempenho do sector, não se tendo logrado travar a redução da produção e da produtividade, o que eventualmente reflecte um ambiente socioeconómico e institucional mais amplo, isto é, além do sector agrário. Na terceira parte, colocam-se alguns elementos de reflexão sobre questões institucionais que possam contribuir para o debate sobre o desenvolvimento futuro do sector agrário. Sugere-se a necessidade de pensar o futuro da Agricultura em Moçambique numa perspectiva de longo prazo, com foco na adopção e estabilização de um quadro institucional orientado para o aumento da produtividade agrária e para a preservação do ambiente.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura; institutions / instituições

Desenvolvimento económico e instituições em Moçambique: Factores que afectam a gestão das finanças públicas - Cruz, António S.; Mafambissa, Fausto J. (2020)
Moçambique alcançou um desenvolvimento socioeconómico incipiente mas ainda frágil, desde 1975. Apesar de o sistema de gestão das finanças públicas ter sido reformado e melhorado, o seu desempenho tem vindo a enfraquecer desde 2013. Utilizando uma abordagem económica institucional, identificámos a estratégia de crescimento económico, o princípio da separação de poderes e o grau de descentralização como factores-chave que afectam o sistema de gestão das finanças públicas. Como a actual estratégia baseada nos recursos naturais parece estar a falhar, sugerimos uma estratégia alternativa de crescimento balanceado no contexto de um sistema político democrático efectivo. Isso implicaria a identificação de políticas prioritárias necessárias para promover um desenvolvimento sustentável e inclusivo.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; institutions / instituições

Economic development and institutions in Mozambique: Factors affecting public financial management - Cruz, António S.; Mafambissa, Fausto J. (2020)
Abstract: Mozambique has achieved incipient but still fragile socio-economic development since 1975. The public financial management system has been reformed and improved, but its performance has weakened since 2013. Applying an institutional economics approach, we have identified the economic growth strategy, the separation of powers principle, and the degree of decentralization as key factors affecting the public financial management system. As the current strategy based on natural resources seems to be failing, we suggest an alternative balanced growth strategy in the context of an effective democratic political system. It would entail the identification of policy priorities required for fostering sustainable and inclusive development.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; budget / orçamento; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; institutions / instituições

Reformas de descentralização em Moçambique: o papel das instituições na definição dos resultados - Forquilha, Salvador (2020)
Com a introdução das reformas económicas nos finais dos anos 1980 e a abertura do espaço político e o fim da guerra civil no início dos anos 1990, teve início em Moçambique o processo de descentralização. Diferentes pesquisas desenvolvidas nos últimos anos mostram que, à semelhança do que acontece em outros países da África subsaariana, o impacto das reformas de descentralização na promoção do desenvolvimento local e no aprofundamento da democracia em Moçambique é modesto. Como explicar esse impacto modesto? Com base em três reformas importantes do processo da descentralização em Moçambique, nomeadamente os '7 milhões', a municipalização e a governação descentralizada provincial, este artigo procura responder à pergunta analisando a maneira como diferentes dimensões das instituições afectam os resultados das reformas. O argumento principal do artigo sublinha a ideia segundo a qual os resultados das reformas de descentralização em Moçambique são condicionados pela natureza e pelos mecanismos do funcionamento do sistema político. Entre os factores/constrangimentos institucionais, a capacidade do Estado e autonomia face aos interesses privados, particularmente de grupos políticos, destacam-se nas três reformas analisadas ao longo deste artigo. Neste contexto, as reformas cristalizam a maneira como os interesses de grupos, particularmente políticopartidários, capturam o Estado e as usam como um mecanismo de manutenção e reforço do poder político. Nesse sentido, a descentralização, mais do que um meio para a melhoria da provisão de serviços públicos e o aprofundamento da democracia, funciona como um instrumento para o reforço do controlo do Estado e a acomodação das elites. Provavelmente, este é o maior desafio que a descentralização enfrenta em Moçambique e, por isso, constitui um aspecto fundamental a tomar em conta em qualquer reforma nessa área, no contexto do aprofundamento da democracia e da promoção do desenvolvimento local.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; institutions / instituições

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Saúde, desenvolvimento e factores institucionais: o caso de Moçambique - Garrido, Paulo Ivo (2020)
Este texto tem por objectivo central mostrar o impacto que as instituições têm no desempenho do sector da Saúde em Moçambique. No texto demonstra-se que, de entre os Determinantes Sociais da Saúde, as instituições têm um papel central no desempenho do sector da Saúde — e, por seu intermédio, no desenvolvimento económico e social — dos moçambicanos, em especial dos mais pobres e mais vulneráveis, como as crianças, as mulheres, as pessoas com deficiência e os idosos. Argumenta-se também que as deficiências e ineficiências do funcionamento do sector da Saúde em Moçambique resultam em larga medida do facto de as instituições com influência no sector da Saúde serem controladas por uma minoria de privilegiados que não dá a prioridade devida às necessidades básicas em saúde da maioria da população. Finalmente, argumenta-se que as medidas de carácter institucional mais importantes para a melhoria do estado de saúde dos moçambicanos são a revisão da Constituição da República, o reforço do Sistema Nacional de Saúde (em particular do Serviço Nacional de Saúde) e a redução da pobreza e das iniquidades económica e social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Natural resources, institutions, and economic transformation in Mozambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
In the light of Mozambique’s natural resources boom—especially its large-scale investments in mining, oil, and gas—this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review—documental and bibliographic—and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique’s political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Recursos naturais, instituições e transformação económica em Moçambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
Face ao boom de recursos naturais em Moçambique — em especial dos seus grandes investimentos em exploração mineira, petróleo e gás —, este documento analisa a perspectiva de as indústrias extractivas contribuírem para a transformação económica de um ponto de vista institucional. Para esse efeito, abordamos a dinâmica institucional do sector dos recursos e consideramos as causas subjacentes aos resultados identificados. É discutida a Estratégia Nacional de Desenvolvimento enquanto instrumento que apresenta a visão para a transformação e diversificação económica. O documento baseia-se numa revisão documental e bibliográfica e em dados primários recolhidos pelos autores no âmbito da sua investigação no campo dos recursos naturais e da economia política do desenvolvimento. Concluímos que, dado o patrocínio político e o clientelismo de Moçambique, a competição no interior da elite governante, a base produtiva limitada, a fraca capacidade do Estado, o elevado nível de pobreza e os défices fiscais recorrentes, as perspectivas de que o actual boom de recursos leve à transformação económica, apesar do seu considerável potencial, são, na melhor das hipóteses, incertas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Análise de Economia Política da Governação Local Moçambique - Eurosis (Mozambique Monitoring and Evaluation Mechanism and Services (MMEMS), 2020)
A governação local em Moçambique continua a desenvolver-se em duas vertentes: a desconcentração de poderes, através dos órgãos locais do Estado (secretarias de Estado da província, administrações distritais, etc), e a devolução do poder através dos órgãos de poder local (presidentes de conselhos autárquicos e governadores provinciais eleitos). O processo de criação de autarquias tem sido muito lento e a maioria dos cidadãos vive em áreas geridas pelos órgãos locais do estado e não por órgãos eleitos directamente por si. Não é ainda claro como vai funcionar a administração pública no novo figurino que criou a representação do Estado nas províncias onde existem governadores eleitos e um governo estabelecido. O que é claro, é a forte tendência para a centralização do partido político no poder e para a intervenção directa na gestão local da coisa pública, o que afecta a inclusão, transparência e prestação de contas em todas as áreas de governação. O quadro de políticas e legal é disperso e omisso em relação a como se realiza a participação dos cidadãos e cidadãs na governação em geral e como se promove a inclusão, transparência e prestação de contas. É também limitado o quadro em que operam serviços fundamentais para a transparência da administração pública, como por exemplo, os serviços de inspecção de saúde e educação, cujo quadro regulatório limita o potencial destas intervenções. Este contexto cria oportunidades para o exercício de poder discricionário a todos os níveis e leva a que intervenções fiquem dependentes do interesse político dos líderes aos vários níveis para a sua implementação. Num contexto de uma corrupção generalizada, isto é um obstáculo à realização de actividades e sustentabilidade das intervenções. Apesar das limitações apontadas, existem oportunidades e espaços para promover uma maior participação dos cidadãos e melhor prestação de contas do sector público, os quais podem ser usados como base para novas intervenções. Assim, apesar da ausência de um bom quadro legal, há alguma legislação e posições públicas do governo que remetem para um primado do cidadão, para um serviço público de qualidade e inclusivo e para o combate à corrupção. Há também mecanismos e processos que assumem a participação informada dos cidadãos nos processos de decisão sobre questões do desenvolvimento em geral (IPCC, assembleias autárquicas e provinciais) e da saúde e educação em particular (comités das unidades de serviços). Existem formalmente instituições e processos que têm como função garantir uma administração pública isenta e de qualidade (inspecção, tribunais administrativos provinciais, gabinetes anticorrupção). O nível de funcionamento destes mecanismos e processos varia muito e está dependente do interesse dos governantes locais, da mobilização comunitária e dos recursos existentes). Assim, pode dizer-se que há uma base para sobre a qual trabalhar para conseguir mais transparência, prestação de contas e inclusão ao fortalecer a governação local ao nível provincial, distrital e local (da unidades de prestação se serviços). Também o apoio à inspecção de saúde e educação pode contribuir para a melhoria da qualidade de serviços prestados aos cidadãos ao assegurar um melhor seguimento das regras e protocolos de prestação de serviços. É importante notar, contudo, que para além dos obstáculos acima referidos, o presente momento coloca desafios particulares ao desviar a atenção do governo para a resposta aos conflitos armados e à pandemia do COVID-19.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; GP - Nampula; GP - Zambézia; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; education / educação; governance / governação; health / saúde; institutions / instituições

Faith communities, youth and development in Mozambique - Chifeche, Victoria; Dreyer, Yolanda (HTS Teologiese Studies / Theological Studies, 2019)
In Mozambique, poverty is pervasive because of factors such as the civil war (1976–1992) and its aftermath, political instability, food scarcity and natural disasters. This article elucidates the situation of post-civil war Mozambique from a socio-political perspective with a specific focus on children and the youth as a particularly vulnerable group. Many children and young people have been displaced and are subject to work exploitation and sexual abuse. Female children also fall victim to the cultural practice of child marriage. The absence of comprehensive social measures for the protection of vulnerable young persons has a detrimental effect on their welfare and future prospects. The aim of the article is to explore the role that faith communities and church institutions can play in this context. From an inclusive congregational perspective, the inclusion of youth in all aspects of faith communities as a strategy for development is discussed. From a human rights and theological perspective, participatory action is required for faith communities and church institutions to contribute to making a life of human dignity possible for children and young people.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; institutions / instituições; youth / juventude

‘Goats eat where they are tied up’: illicit and habitual corruption in Mozambique - Tvedten, Inge; Picardo, Rachi (Review of African Political Economy, 2018)
The article shows that corruption is structural and omnipresent in Mozambican society, eﬀectively legitimising corrupt practices at all levels. Using an anthropological approach, it argues that smallscale corruption has the most immediate eﬀects for the urban and rural poor and is so common that it has become an integrated part of daily life, or ‘habitual’. While most of the poor relate to corruption through tacit acceptance and acts of compliance, its practical implications are most severe for the very poorest, who cannot aﬀord to take part in corrupt exchanges and are excluded from vital social relationships and social services. A few case studies included re: Northern Moz.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; corruption / corrupção; institutions / instituições; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Capacity Strengthening in the Least Developed Countries (ldcs) for Adaptation to Climate Change (clacc): Climate Change and Health in Mozambique - Bambaíge, Albertina João; Cuamba, Boaventura; Hauengue, Maria dos Anjos (International Institute for Environment and Development (IIED), 2008)
The relationship between climate change and its effects on human health has been widely studied. Increases in temperature and variations in precipitation can exacerbate a number of human diseases including respiratory infections, malnutrition, vector and water borne diseases such as malaria and cholera. Besides all efforts undertaken by the Mozambican Government to reduce poverty and meet the MDGs targets, it is clear that climate change effects will influence negatively in meeting these targets. Damages caused by floods in Mozambique undermine economic growth rates of the country. Mainstreaming climate change adaptation into government policies would strengthen the capacity of the country to deal with climate change impacts. Climate change is a reality and the impacts on health are great with the poor at most risk. Efforts must be done nationally at all levels to come up with a proactive approach since all actors in the Mozambican society are directly or indirectly affected. This must include clear policies and strategies to deal with impacts of climate change on health; intersectoral approaches for strengthening the implementation of these policies and a greater support from those wealthy in resources and knowledge for minimizing the risks and increase community's adaptation capacity. The case study included in this country report highlights the relationship between climate change and human health through an analysis of malaria and cholera data taking the example of the 2000/2001 floods, which were considered the worst in the last fifty years. Adaptation practices and the adaptive capacity of the country during floods periods, policies and strategies are also discussed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; government policy / politica governamental; health / saúde; institutions / instituições; natural disasters / desastres naturais

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência

The resource curse: which institutions matter? - Kolstad, Ivar; Chr. Michelsens institutt (Chr. Michelsen Institute, 2007)
Two types of models are dominant in the current resource curse literature. One type of model studies the selection of entrepreneurs into rent-seeking versus productive activities. The other type analyses the use of patronage by politicians seeking re-election. The policy implications of the two models are quite different. The first model suggests that institutions governing the private sector ought to be improved. The second model suggests that institutions governing the public sector should be emphasized. This article empirically tests the impact of the private versus public sector institutions on the resource curse, using cross-country data from Sachs and Warner (1997a) and Polity IV. The main result is that only improved private sector institutions ameliorate the resource curse.
Keywords: L - english / inglês; institutions / instituições; natural resources / recursos naturais

Investigação sobre Mulher e Género no Centro de Estudos Africanos - Casimiro, Isabel Maria; Adrare, Ximena (Estudos Moçambicanos, 2005)
Os estudos sobre as relações sociais entre homens e mulheres - das relações de Género - começaram a ganhar corpo a partir de finais da década de 60 os países de língua inglesa - onde foi onstruída a categoria de Género (Gender) - mas depressa se expandiram pelo mundo. Género como categoria análitica, foi e continua a ser o resultado duma interrogação feminista no sentido de esclarecer a subalternidade e subordinação das mulheres no mundo. Trata-se de uma procura que caminhou que continua a caminhar no sentido de interrogações. Não pretendem as suas criadoras feministas o esclarecimento contemplativo por si acerca da discriminação das mulheres. Moveu-as e move-as o desejo de alterar as relações desiguais entre mulheres e homens, no âmbito de construções identitárias que marcam a discriminação entre os seres humanos baseada num poder hierárquico característico do mundo em que vivemos, com o propósito de o transformar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; institutions / instituições; ⛔ No DOI found

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições